Toll-Like Receptors 2020
DOI: 10.5772/intechopen.84679
|View full text |Cite
|
Sign up to set email alerts
|

TLR-Mediated Host Immune Response to Parasitic Infectious Diseases

Abstract: Toll-like receptors (TLRs) are important for the host immune response to a variety of pathogens, including bacteria, viruses, fungi, and parasites. These receptors become activated upon recognizing pathogen-associated molecular patterns (PAMPs) and thus initiate the innate immune response to the corresponding pathogen. A key aspect of TLRs is their activation of signaling that leads to cytokine production and an inflammatory response. Additionally, TLRs act as the bridge between innate and acquired immunity, e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 115 publications
(108 reference statements)
0
5
0
Order By: Relevance
“…TLR4 immune receptor is involved in recognizing pathogenic proteins, which in turn triggers the generation of inflammatory cytokines. Numerous studies have reported that TLR4 is essential for generating innate immune responses against an array of infections ( 61 , 62 ). The molecular docking studies were carried out to evaluate the molecular interactions between vaccine constructs.…”
Section: Resultsmentioning
confidence: 99%
“…TLR4 immune receptor is involved in recognizing pathogenic proteins, which in turn triggers the generation of inflammatory cytokines. Numerous studies have reported that TLR4 is essential for generating innate immune responses against an array of infections ( 61 , 62 ). The molecular docking studies were carried out to evaluate the molecular interactions between vaccine constructs.…”
Section: Resultsmentioning
confidence: 99%
“…As far as parasites are concerned, the highlighted SNP was only analyzed for malaria (in one study), with no significant association. At the molecular level, this receptor can function as an upstream sensor for GSPL and induce the intracellular inflammatory signaling necessary to kill parasites ( Aguirre-García et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…In this context, Toll-like Receptors ( TLRs ) are genes that encode transmembrane receptors of the same name (TLR1-10) present in mammals and are responsible for inducing the innate immune response by recognizing pathogen-associated molecular patterns (PAMPs) and molecular damage associated pathogens (DAMPs) through antigen presenting cells (APCs) ( Aguirre-García et al., 2019 ). As pattern recognition receptors (PRRs), TLRs regulate the generation of cytokines and indirectly activate the adaptive immune system in addition to inducing the innate immune system.…”
Section: Introductionmentioning
confidence: 99%